OsIAA18, an Aux/IAA Transcription Factor Gene, Is Involved in Salt and Drought Tolerance in Rice - Wang, Feibing; Niu, Haofei; Xin, Dongqing; Long, Yi; Wang, Guangpeng; Liu, Zongmei; Li, Gang; Zhang, Fan; Qi, Mingyang; Ye, Yuxiu; Wang, Zunxin; Pei, Baolei; et al. (Frontiers in Plant Science, 2021)
Auxin/indoleacetic acid (Aux/IAA) proteins play an important regulatory role in developmental process and the responses to stresses of plants. The previous study has shown that constitutive expression of rice Aux/IAA transcription factor gene OsIAA18 improved salt and osmotic tolerance in transgenic Arabidopsis plants. However, little work is known about the regulatory functions of the OsIAA18 gene in regulating abiotic stress tolerance of rice. In this study, the OsIAA18 gene was introduced into rice cultivar Zhonghua 11 and the OsIAA18 overexpression rice plants exhibited significantly enhanced salt and drought tolerance compared with the wild-type (WT). Moreover, overexpression of OsIAA18 in rice increased endogenous ABA levels and the OsIAA18 overexpression rice plants showed hypersensitive to exogenous ABA treatment at both germination and post-germination stages compared to WT. Overexpression of OsIAA18 up-regulated the genes involved in ABA biosynthesis and signaling pathways, proline biosynthesis pathway and ROS-scavenging system in the OsIAA18 overexpression rice plants under salt and drought stresses. Proline content, superoxide dismutase (SOD) and peroxidase (POD) activities were significantly increased, whereas malonaldehyde (MDA), hydrogen peroxide (H2O2) and superoxide anion radical (O2-) content were significantly decreased in the transgenic plants under salt and drought stresses. Taken together, we suggest that OsIAA18 plays a positive role in drought and salt tolerance by regulating stress-induced ABA signaling. The OsIAA18 gene has potential application in genetically modified crops with enhanced tolerance to abiotic stresses.